(untitled) (ModaPalavra e-periódico, 2024)
Events are considered, by most of the literature, the most efficient means of communication for publicizing brands and launching products and brands. Fashion commercial brands mainly benefit from fashion shows as events aimed at buyers, the press, and end consumers. This article analyzes the feelings, emotions, and sensations aroused in a conceptual fashion show. Its motto resides in the presentation entitled The mud show by the Balenciaga brand for the Spring/Summer 2023 season (occurred in October 2022 in Paris). Thus, the methodology that guided this research involved a descriptive analysis based on the triangulation between the observed fashion shows, the data collected in legitimate journalistic publications in the field of fashion, and the theoretical reference consulted through bibliographical research. We concluded that The mud show properly applied expressive elements such as the choice of casting, scenography, sound, lighting, and mainly its theme to sensitize and move the spectators.